Double diffusion on unsteady magnetohydrodynamic free convection flow in a rotating medium - Lim, Yeou Jiann (2014)
The heat and mass transfer on the unsteady radiative magnetohydrodynamic (MHO) free convection flow over an impulsively started vertical plate in a rotating medium is studied. The fluid is considered gray, absorbing-emitting but non-scattering medium and the Rosseland approximation is used to describe the radiative heat flux in this analysis. The Laplace transform technique is used to obtain the exact solutions of the governing equations. The numerical results of fluid velocity, fluid temperature, fluid concentration, and skin friction, as well as the rate of heat transfer and the rate of mass transfer at the plate are displayed through graphs and tables in order to see the effects of the various parameters involved. The present results obtained here may be used to verify the validation of obtained numerical solutions for more complicate fluid flow problems.